2021
DOI: 10.1016/s1473-3099(21)00076-1
|View full text |Cite
|
Sign up to set email alerts
|

Bell's palsy and SARS-CoV-2 vaccines

Abstract: health-coronavirus-who-vaccines/under-pressure-who-plans-covid-19vaccine-insurance-scheme-for-poor-nations-idINKBN27E2E6 (accessed Jan 27, 2021).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
157
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(168 citation statements)
references
References 10 publications
10
157
1
Order By: Relevance
“…Dear Editor, During pandemic influenza A (H1N1) vaccination campaign in 2009, relative risk for Bell's palsy (BP) following vaccine increased significantly [1]. Combining data from both SARS-CoV-2 Pfizer-BioNTech and Moderna vaccine trials, Ozonoff et al [2] suggest an imbalance in the incidence of BP following vaccination (seven cases) compared with the placebo group (one case). The US Food and Drug Administration (FDA) pointed out that a causal relationship between the COVID-19 vaccines and BP cannot be definitively excluded and consequently, recommended strict pharmacovigilance for BP after COVID-19 vaccination in large populations [3].…”
mentioning
confidence: 99%
“…Dear Editor, During pandemic influenza A (H1N1) vaccination campaign in 2009, relative risk for Bell's palsy (BP) following vaccine increased significantly [1]. Combining data from both SARS-CoV-2 Pfizer-BioNTech and Moderna vaccine trials, Ozonoff et al [2] suggest an imbalance in the incidence of BP following vaccination (seven cases) compared with the placebo group (one case). The US Food and Drug Administration (FDA) pointed out that a causal relationship between the COVID-19 vaccines and BP cannot be definitively excluded and consequently, recommended strict pharmacovigilance for BP after COVID-19 vaccination in large populations [3].…”
mentioning
confidence: 99%
“…Ideally, these systems should use databases that can be accessed in near real time to identify large numbers of individuals who have been vaccinated, ascertain the vaccine and lot number administered, and detect adverse events using validated coding algorithms, such as those developed by the Brighton Collaboration. 30 These systems could address concerns regarding cases of Bell's palsy observed in phase III trials of the messenger RNA based vaccines developed by Pfizer-BioNTech (BNT162b2) and Moderna (mRNA-1273) 31 by comparing incidence of this outcome against background rates in the general population and matched non-vaccinated comparison groups.…”
Section: Making Vaccine Safety Surveillance Workmentioning
confidence: 99%
“…Despite geographical and seasonal variations, 3 , 4 the generally agreed incidence of Bell's palsy is 15–30 cases each year per 100 000 population. Ozonoff and colleagues 2 rightly state that the predicted 12-month (annual) incidence of Bell's palsy inferred from mRNA vaccine trials is higher than that reported during the 2-month observation period of these studies. They concluded that the observed incidence of Bell's palsy in the mRNA vaccine arms was 3·5 to seven times higher than expected in the general population.…”
mentioning
confidence: 95%
“…In their Comment, Al Ozonoff and colleagues 2 considered key statistical and epidemiological aspects of SARS-CoV-2 vaccine trial safety data regarding the onset of facial paralysis. Here, we offer a different interpretation of their findings and statistical consideration of risks associated with mRNA and non-mRNA SARS-CoV-2 vaccines.…”
mentioning
confidence: 99%